Development of an adaptive neuro-controller and satellite simulator for nano-satellite attitude control system - Siti Maryam Sharun (School of Mechatronic Engineering, 2013)
The purpose of this research is to improve the triaxial control scheme, for stabilizing system of nano-satellite which is an Innovative Satellite (InnoSAT) and developing a satelit simulator in order to validate the controller that have been developed. Four controllers were introduced in this research, namely Adaptive Neuro-Controller (ANC) based on Hybrid Multi Layered Perceptron (HMLP), ANC based on Multi Layered Perceptron (MLP), Adaptive Parametric Black Box (APBB) controller and Modified Proportional, Integral and Derivative (MPID) controller.